A combined hands‐on teaching programme and clinical pathway focused on pleural ultrasound and procedure supervision transforms pleural procedure outcomes. Issue 11 (5th November 2017) - Edwards, Timothy; Cook, Alistair; Salamonsen, Matthew; Bashirzadeh, Farzad; Fielding, David
Abstract : Background: Management of pleural effusions is a common diagnostic and management problem. Aims: We reviewed the outcomes from pleural procedures after the instigation of pleural effusion management guidelines, focusing on pleural ultrasound and a hands‐on teaching programme followed by procedure supervision that enabled many operators to perform such procedures. Methods: This is a retrospective analysis of all procedures performed for pleural effusions on medical patients. Outcomes were assessed prior to the instigation of pleural effusion management guidelines (pleural pathway) and hands‐on teaching (January 2010 to June 2011) and following these interventions (January 2012 to June 2013). Results: A total of 171 procedures involving 129 patients (pre‐pathway group) and 146 procedures involving 115 patients (post‐pathway group) was analysed. The rate of complications prior to the pleural pathway was 22.2% (38 of 171 procedures). Following the pathway, the rate of complications declined to 7.5% (11 of 146 procedures, P  < 0.003). The use of pleural ultrasound increased dramatically (72.5 vs 90.2%). The number of patients who underwent repeated procedures (defined as ≥3) reduced dramatically (21 vs 7, P  < 0.01). This improvement occurred using many supervised operators who completed the hands‐on teaching programme ( n  = 32) and followed the pleural pathway (127 of 146 procedures). Conclusion: The instigation of a clinical pathway focused on the use of bedside pleural ultrasound, and teaching of drainage techniques with procedure supervision vastly improved patient outcomes. This not only allowed better quality of care for patients, it also provided the acquisition of new skills to medical staff, not limiting these skills to specialised staff.